ANALISIS PROFESIONALISME GURU PAUD: STUDI KASUS GURU DI BALMORAL PRESCHOOL PADANG DALAM PERBANDINGAN PRAKTIK PENDIDIKAN INDONESIA, MALAYSIA, DAN SINGAPURA - Siti Rahmi Cahyati; Hanifah Aulia Yunefa; Delfi Eliza (STKIP Subang, 2026)
This study aims to analyze the professionalism of early childhood education (ECE) teachers at Balmoral Preschool Padang through a comparison of educational practices in Indonesia, Malaysia, and Singapore, focusing on teacher competencies based on different educational backgrounds. The study employed a qualitative method with a case study approach. Data were collected through observations, in-depth interviews, and documentation involving teachers and the principal at Balmoral Preschool Padang. The findings revealed that out of 13 teachers, only 2 had an educational background in Early Childhood Education (ECE), while the others came from different majors such as English, Psychology, Fine Arts, and Indonesian Language. Teachers with an ECE background demonstrated better pedagogical competence in understanding child development, designing play-based learning, and conducting child development assessments. Meanwhile, non-ECE teachers contributed positively to the learning process through bilingual communication skills, artistic creativity, and psychological understanding of children.The study also found that differences in educational backgrounds caused some teachers to experience difficulties in understanding the ECE curriculum and implementing appropriate early childhood learning strategies. Compared to Malaysia and Singapore, the professionalism of ECE teachers in Indonesia still faces challenges in terms of competency standardization and professional certification. This study concludes that diverse educational backgrounds can become a strength in early childhood learning if supported by continuous professional training and the strengthening of pedagogical competencies in early childhood education. Keywords: Early Childhood Teacher Professionalism, Teacher Competence, Educational Background, Case Study, Early Childhood Education ABSTRAK Penelitian ini bertujuan untuk menganalisis profesionalisme guru PAUD di Balmoral Preschool Padang melalui perbandingan praktik pendidikan di Indonesia, Malaysia, dan Singapore dengan fokus pada kompetensi guru berdasarkan latar belakang pendidikan yang berbeda. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus. Data diperoleh melalui observasi, wawancara mendalam, dan dokumentasi terhadap guru dan kepala sekolah di Balmoral Preschool Padang. Hasil penelitian menunjukkan bahwa dari 13 guru yang mengajar, hanya 2 guru yang memiliki latar belakang Pendidikan Anak Usia Dini (PAUD), sedangkan guru lainnya berasal dari jurusan Bahasa Inggris, Psikologi, Seni Rupa, dan Bahasa Indonesia. Guru berlatar belakang PAUD memiliki kemampuan pedagogik yang lebih baik dalam memahami perkembangan anak, merancang pembelajaran berbasis bermain, dan melakukan asesmen perkembangan anak. Sementara itu, guru non-PAUD memberikan kontribusi positif dalam pembelajaran melalui kemampuan bilingual, kreativitas seni, dan pemahaman psikologis anak. Penelitian ini juga menemukan bahwa perbedaan latar belakang pendidikan menyebabkan beberapa guru mengalami kesulitan dalam memahami kurikulum PAUD dan strategi pembelajaran anak usia dini. Dibandingkan dengan Malaysia dan Singapura, profesionalisme guru PAUD di Indonesia masih menghadapi tantangan dalam standarisasi kompetensi dan sertifikasi profesi. Penelitian ini menyimpulkan bahwa keberagaman latar belakang pendidikan dapat menjadi kekuatan dalam pembelajaran PAUD apabila didukung dengan pelatihan profesional berkelanjutan dan penguatan kompetensi pedagogik anak usia dini. Kata Kunci: Profesionalisme Guru PAUD, Kompetensi Guru, Latar Belakang Pendidikan, Studi Kasus, Pendidikan Anak Usia Dini